Improving Student Learning Outcomes by Implementing the Numbered Heads Together Model in Islamic Education Learning at SD Negeri Seumantok - Nurfadhilah; Diana (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to improve student learning outcomes in Islamic Education learning through the implementation of the Numbered Heads Together (NHT) cooperative learning model at SD Negeri Seumantok. The research employed a Classroom Action Research (CAR) design consisting of two cycles, with each cycle including the stages of planning, action, observation, and reflection. The participants of this study were 26 fifth-grade students. Data were collected through learning outcome tests, observation sheets of teacher and student activities, and documentation. The collected data were analyzed using descriptive quantitative and qualitative techniques. The results showed a significant improvement in students’ learning outcomes after the implementation of the NHT model. In the pre-cycle, the average student score was 62.15, with only 38.46% of students achieving mastery learning. After the implementation of NHT in Cycle I, the average score increased to 72.30, and the mastery learning percentage rose to 65.38%. Furthermore, in Cycle II, the average score improved to 84.10, with mastery learning reaching 88.46%, indicating that most students had achieved the minimum competency standard. Observation results also revealed improvements in classroom engagement, as student participation increased from 60% in Cycle I to 85% in Cycle II, while teacher performance improved from 70% to 90%. These findings demonstrate that the Numbered Heads Together model effectively enhances student learning outcomes by promoting active participation, collaboration, and responsibility in group learning. Therefore, the NHT model is recommended as an effective instructional strategy for improving Islamic Education learning outcomes in elementary schools.